Organizational commitment and intention of permanence of nursing professionals in a private health institution, Lima - Contreras Alomía, Irma Aurora (2018)
Objective: the verification of the existence of a direct relationship between the variables of organizational commitment and the intention of permanence in the nursing staff of a private health institution in Lima - Peru. The values according to Meller and Allen (1991) and the percentage of employees who intended to remain in the institution. Material and methods: the study was correlational quantitative, not experimental, transversal and descriptive. It had as a population all the nurses of that establishment adding a total of 120 professionals. The sample consisted of 100 nurses selected by non-probabilistic sample according to convenience, of which 81 collaborators filled out the data collection instrument correctly. Results: the prevailing commitment is the affective one (93.8%), the continuation commitment follow-up (76.5%); However, the normative commitment (35.8%) is present in a small percentage. 90.1% of the collaborators intend to remain in the institution. Conclusion: there is no significant relationship between the organizational commitment and the intention of permanence of nursing professionals.